2007
DOI: 10.2460/ajvr.68.12.1319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influences of exercise, birth date, and osteochondrosis on plasma bone marker concentrations in Hanoverian Warmblood foals

Abstract: An age-related decrease in concentrations of bone markers was seen during the first 200 days of life. Changes in bone marker concentrations were similar for foals with osteochondrosis and healthy foals. The correlation between the decrease in bone marker concentration and date of birth indicates that there are differences in skeletal development between early- and late-born foals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
4
5
0
3
Order By: Relevance
“…The above mentioned studies deal with subjects, which have been diseased over months and years. There, a significant decrease of the bone markers was observed over time, which seems to be physiological, since this has already been shown in other studies (Price et al 2001, Vervuert et al 2007, Hüttenmoser (2006.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The above mentioned studies deal with subjects, which have been diseased over months and years. There, a significant decrease of the bone markers was observed over time, which seems to be physiological, since this has already been shown in other studies (Price et al 2001, Vervuert et al 2007, Hüttenmoser (2006.…”
Section: Discussionsupporting
confidence: 50%
“…In a study with foals on osteochondrosis, Vervuert et al (2007) showed no differences between animals with osteochcondrosis compared to those without when comparing the osteocalcin concentrations in serum, which is a bone formation marker. In contrast, Billinghurst et al (2004) demonstrated that bone marker concentrations differ between diseased and healthy animals in the first year of the foal's life.…”
Section: Discussionmentioning
confidence: 99%
“…ICTP reflects the amount of organic matrix being disrupted in alveolar bone (specifically collagen type I) following osteoclastic bone resorption. ICTP has been utilized as a bone resorption marker in several systemic disease states including osteoarthritis (Berger et al 2005), rheumathoid arthritis (Chopin et al 2008), osteochondrosis (Vervuert et al 2007), primary tumours and metastasis (Kong et al 2007) and many other skeletal conditions. It has been shown by histological human data that osteoclastic activity peaks immediately after the bone is exposed by surgical operations (Wilderman et al 1970).…”
Section: Discussionmentioning
confidence: 99%
“…An age-related decrease in concentrations of bone markers was also seen in Hanoverian foals during the first 200 days of life. These changes were correlated to the date of birth indicating that there are differences in skeletal development between earlyand late-born foals (Vervuert et al 2007). OC levels were also observed to change in relation to the season with higher concentrations during winter (Pastoret et al 2007).…”
Section: Introductionmentioning
confidence: 85%